2021
DOI: 10.1371/journal.pone.0255920
|View full text |Cite
|
Sign up to set email alerts
|

Association of leptin G2548A and leptin receptor Q223R polymorphisms and their serum levels with infertility and recurrent pregnancy loss in Iranian women with polycystic ovary syndrome

Abstract: Background Adipokine leptin plays a crucial role in metabolic and reproductive functions. Leptin receptor has a soluble form that binds to leptin, thus modulating its level in the circulation. It has been indicated that the levels of leptin and leptin receptor and also LEP rs7799039 and LEPR rs1137101 polymorphisms are associated with metabolic disorders. In the present study, we assessed the levels of leptin and soluble leptin receptor (sOB-R), and also the frequency of rs7799039 and rs1137101 polymorphisms i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 57 publications
0
6
0
1
Order By: Relevance
“…Studies have shown that Leptin enhanced the expression of aromatase genes by activating classic signal transduction pathways MAPK and PI3K, whereas this phenomenon was significantly attenuated in granulosa cells of PCOS patients, together with significantly increased plasma Leptin and decreased soluble Leptin receptor (s OB-R) in PCOS patients ( 80 ). This may suggest that Leptin resistance in PCOS patients may be possibly mediated by Sam68, an RNA-binding protein that is widely expressed in the body and has signaling functions ( 81 ).…”
Section: Methodsmentioning
confidence: 99%
“…Studies have shown that Leptin enhanced the expression of aromatase genes by activating classic signal transduction pathways MAPK and PI3K, whereas this phenomenon was significantly attenuated in granulosa cells of PCOS patients, together with significantly increased plasma Leptin and decreased soluble Leptin receptor (s OB-R) in PCOS patients ( 80 ). This may suggest that Leptin resistance in PCOS patients may be possibly mediated by Sam68, an RNA-binding protein that is widely expressed in the body and has signaling functions ( 81 ).…”
Section: Methodsmentioning
confidence: 99%
“…A common variant of the -2548G>A (rs7799039) leptin promoter results in the transition substitution of guanine to adenine at nucleotide position -2548 upstream of the ATG start site [ 15 ]. This variant has previously been reported to be association with elevated serum leptin levels, metabolic syndrome, hypertension and obesity [ 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. On the other hand, there is conflicting information relating to these associations with some studies reporting a positive correlation and some reporting a negative correlation.…”
Section: Introductionmentioning
confidence: 99%
“…Tshori et al [161], Cheng et al [162], Nowzari et al [163], Choi et al [164], Ji et al [165], Huang et al [166], Zhai et al [167], Schiattarella et al [168], Brodehl et al [169], Wu et al [170], Zhao et al [171], Ujihara et al [172], Tan et al [173], Gittleman et al [174], Chen et al [175], Layrisse et al [176], Nakayama et al [177], Zhang et al [178], Vadvalkar et al [179], Burdon et al [180], Steffen et al [181], Ye et al [182], Tao et al [183] and Li et al [184] reported that PLA2G5, CASP1, TNNT2, FOXP3, DRD4, NEURL1, TIMP4, SOCS1, CD74, PLK1, ATF5, GATA6, IRF7, FOXC2, IRF9, FHOD3, BGN (biglycan), CACNA1H, FBLN2, ADAMTS8, COL1A1, POSTN (periostin), VARS2, SOD3, ADAMTS13, FABP5, ADAM23, COL1A2, MST1, ENDOG (endonuclease G), NKX2-6, MYOCD (myocardin), CES1, CYP19A1, PKP2, CD36, SALL1, ARG1, MSR1, S1PR1, OXTR (oxytocin receptor), MITF (melanocyte inducing transcription factor), MSX2, LEPR (leptin receptor), CDH13, PRKCH (protein kinase C eta), AR (androgen receptor), DKK3, FOXO1, CRYAB (crystallin alpha B), B2M, WWP1, FKTN (fukutin), PIK3C2A, KLKB1, CHRNA5, HLA-C, ARRDC4, KCNE3, MPC2, EPHX2, C2, IKZF2, ZBTB20 and RCN2 expressions might be regarded as an indicator of susceptibility to cardiovascular problems. CASP1 [185], FOXP3 [186], SOCS1 [187], GATA6 [188], IRF7 [189], POSTN (periostin) [190], CYP19A1 [191], CD36 [192], LYN (LYN proto-oncogene, Src family tyrosine kinase) [193], CD4 [194], LEPR (leptin receptor) [195], AR (androgen receptor) [196], FOXO1 [197] and PON2 [198] are a potential biomarkers for the detection and prognosis of PCOS. Udjus et al [199] Benjafield et al [200], Shetty et al [58], Kassan et al [201], Wetzl et al [202], Le Hiress et al [203], Pal-Ghosh et al [204], Niu, [205], Fan et al [206], Deng et al [207], Chen et al [208], Sardo et al [209], Seidel et al [210], Zhu et al [211], Omura et al [212], Hu et al [213], Castoldi et al [214], Yoshida et al [215], Palao et al [216…”
Section: Discussionmentioning
confidence: 99%